Implementation and evaluation of hospital-to-home transitional care intervention in patients with chronic heart failure - Zhi-Fen Feng; Yun Liu; Jordan Tovera Salvador; Minerva Bravo De Ala; Mary Ann Cabansag Nery; Xin-Yue Huang; Lei Zhang; Shan Liu (BMC Nursing)
Abstract Background Chronic Heart Failure (CHF) is a complex clinical syndrome that occurs in the end stages of various cardiovascular diseases. It is characterized by symptoms such as weakness, reduced cardiac function, and decreased exercise capacity. The high incidence, high mortality rate, and poor prognosis of CHF have become prominent features of this disease, making it an urgent and pressing clinical issue. Aim This study aims to investigate the impact and evaluate the effectiveness of hospital-to-home transitional care for patients with chronic heart failure (CHF). Methods Convenient sampling was used to select 60 patients with CHF from the cardiology department of a tertiary Grade A hospital in Guangdong Province between February and June 2022. The patients were divided into a control group and an intervention group using a random number table, with 30 patients in each group. The intervention group received a transitional care intervention mainly focused on the transitional care model (TCM), while the control group received routine treatment and interventions for CHF. Results The intervention group showed significantly higher levels of self-efficacy and self-management and better cardiac ultrasound examination results than the control group (P < 0.05). The intervention group also had lower scores in laboratory indicators (plasma NT-pro BNP) than the control group (P < 0.05). Hospital readmission rate: There was no significant difference in hospital readmission rates between the two groups (P > 0.05), but the intervention group showed a significant difference in emergency admission rate (P < 0.05). Conclusions The hospital-to-home TCM enhances self-management and improves the quality of life for patients with chronic heart failure. The conduct of this research provides clinical practitioners with reference for later research, and is also conducive to the promotion and popularisation of health care policies. This study has registered the ethical review batch number, which is NCT06779227. Trial registration The trial has been registered on ClinicalTrial.gov (Ref: NCT06779227). The registration date is January 15, 2025.